Pubertal Pathways in Girls Enrolled in a Contemporary British Cohort - Krista Yorita Christensen; Mildred Maisonet; Carol Rubin; Adrianne Holmes; W. Dana Flanders; Jon Heron; Jean Golding; Michael A. McGeehin; Michele Marcus (International Journal of Pediatrics)
Data from the Avon Longitudinal Study of Parents and Children were used to describe initiation of secondary sexual characteristic development of girls. Tanner stages of breast and pubic hair and menarche status were self-reported via mailed questionnaires, administered from ages 8–14. Initiation pathway was categorized as breast [thelarche] or pubic hair [pubarche] development alone, or synchronous. Average ages at beginning breast and pubic hair development were estimated using survival analysis. Factors associated with initiation pathway were assessed using logistic regression. Among the 3938 participants, the median ages at beginning breast and pubic hair development were 10.19 (95% CI: 10.14–10.24) and 10.95 (95% CI: 10.90–11.00) years. Synchronous initiation was the most commonly reported pathway (46.3%), followed by thelarche (42.1%). Girls in the pubarche pathway were less likely to be obese or overweight at age 8 or have an overweight or obese mother. Girls in the thelarche pathway were less likely to be of nonwhite race or be the third born or later child.